Operando deconvolution of photovoltaic and electrocatalytic performance in ALD TiO(2) protected water splitting photocathodes - Cui, Wei (Royal Society of Chemistry, 2018)

(untitled) (Chem Sci)
In this work, we demonstrate that buried junction photocathodes featuring an ALD TiO(2) protective overlayer can be readily characterized using a variation of the dual working electrode (DWE) technique, where the second working electrode (WE2) is spatially isolated from the hydrogen-evolving active area. The measurement of the surface potential during operation enables the operando deconvolution of the photovoltaic and electrocatalytic performance of these photocathodes, by reconstructing J–ΔV curves (reminiscent of photovoltaic J–V curves) from the 3-electrode water splitting data. Our method provides a clearer understanding of the photocathode degradation mechanism during stability tests, including loss of the catalyst from the surface, which is only possible in our isolated WE2 configuration. A pn(+)Si/TiO(2) photocathode was first investigated as a well behaved model system, and then the technique was applied to an emerging material system based on Cu(2)O/Ga(2)O(3), where we uncovered an intrinsic instability of the Cu(2)O/Ga(2)O(3) junction (loss of photovoltage) during long term stability measurements.